Essential methods for design-based sample surveys : a derivative of Handbook of statistics, Sample surveys: design, methods and applications, vol. 29a - Pfeffermann, Danny; Rao, C. Radhakrishn [ (Calyampudi Radhakrishna)] , 1920- (Elsevier: North-Holland, 2011)
Provides specific aspects of sample survey design, with references to important contributions and available software. This book contains a large variety of applications in specialized areas such as household and business surveys, marketing research, opinion polls and censuses